EPR spectroscopy : Applications in chemistry and biology - Jeschke, Gunnar; Drescher, Malte (Topics in Current Chemistry, 2012)
Sabine Van Doorslaer Damien M. Murphy EPR Spectroscopy in Catalysis Erik Schleicher Stefan Weber Radicals in Flavoproteins Dariush Hinderberger EPR Spectroscopy in Polymer Science Malte Drescher EPR in Protein Science Intrinsically Disordered Proteins Enrica Bordignon Site-Directed Spin Labeling of Membrane Proteins Ivan Krstić Burkhard Endeward Dominik Margraf Andriy Marko Thomas F. Prisner Structure and Dynamics of Nucleic Acids J. van Slageren New Directions in Electron Paramagnetic Resonance Spectroscopy on Molecular Nanomagnets.